Knowledge and Attitude of Population Towards Iodized Salt in Shendi Locality River Nile State in Sudan - Elmanssur, Ahmed Elnadif Ahmed; Elnour, Safa Abdalla; Elmosaad, Yousif Mohammed Ahmed (European Scientific Journal, ESJ, 2017)
Background: Iodine is observed as one of the most important trace elements in the human body, which is considered very essential during the synthesis of thyroid hormones. Iodine deficiency in humans can cause several diseases or problems, which include spontaneous abortion, increased infant mortality, cretinism, goiter, and mental defects. Methods: The study was conducted as a community based descriptive crosssectional study to determine the knowledge and attitude of the population towards iodized salt in Shendi locality, River Nile State, Sudan, during the period of 2013. In this study, 636 households were included. Questionnaire and observations were used as tools for data collection. The households were selected through a multistage cluster-sampling technique, 636 respondents were selected through systemic random sampling. Results: The study found that the knowledge of the respondents about iodized salt was poor. Out of 636 subjects, 356 (56%) were aware of iodine as a nutritional element. 279 (43.9%) identified that iodine is a chemical element. More than half of the respondents, 355(55.8%), were aware of sources of iodine in foods. The data showed that 299 (47%) of the respondents were aware of the main type of food which contains iodine. 356(56%) were aware of the fact that iodine deficiency had significant influence on the body. In addition, study revealed that 261(41%) of participant were aware of iodized salt. Only 48% of the population knew that iodized salt is necessary to alleviate iodine deficiency disorder. Conclusion: Based on our findings, we conclude that the household has poor knowledge, negative attitude, and poor practice about iodized salt. Hence, health authority should have to develop health education programs to increase the awareness of households about the significance of iodized salt. Also, it involves a proper handling of a continual and effective use of media for broadcasting health education programs.